Predicting the underlying factors of academic dishonesty among undergraduates in public universities: a path analysis approach - Imran, Adesile; Nordin, Mohamad Sahari (Springer Science +Business Media Dordrecht, 2013)
Buildingonthemodifiedtheoryofplannedbehavior(TPB),thisstudyexaminedthe underlying psychological motives for academic dishonesty in a sample of 250 undergraduates drawnfromthreeselectedMalaysianpublicuniversities.Theresultsyieldedadditionalsupports for usefulness of modified TPB model in predicting academic misconduct. All components of the model exerted statistically significant effects on intention towards academic misconduct, and intention itself exerted a statistically significant impact on academic dishonesty. This suggeststhatstudents’ academicmisconductscouldbeaddressedeffectivelyifproperattention is given to the underpinning factors. Further, the findings revealed that the hypothesized relationships among variables of the modified model were all statistically significant. The uniqueness of this study lies in the large amount of variance (69 % and 75 %) explained by componentsofthemodel(inthepredictionofintentionandacademicdishonestyrespectively). These variances have rarely been accounted for in the previous studies. Implications of the findings are discussed and suggestions advanced for future studies.